Chronic Emergency : Why NCDs Matter - Nikolic, Irina A.; Stanciole, Anderson E.; Zaydman, Mikhail (World Bank, Washington, DC, 2013)
'Chronic emergency: why non communicable diseases (NCDs) Matter' examines the magnitude of the challenge posed by NCDs in middle- and low-income countries, and makes the case for elevating the challenge as a priority item to address on the agenda of decision-makers. NCDs are on the rise in all middle- and low-income country regions. By 2030, NCDs are expected to account for three quarters of the disease burden in middle-income countries, up from two-thirds today and approaching the level of high-income countries. In low income countries, the NCD share of the disease burden will increase even more quickly and will approach the levels currently found in middle-income countries. At the same time, many low-income countries will continue to contend with substantial communicable disease burdens, thus facing a double burden of disease. Further, compared to their higher-income counterparts, many developing countries will face elevated NCD levels at earlier stages of economic development and with a much compressed timeline to address the challenge. The overall economic and social cost of NCDs vastly exceeds their direct medical costs. NCDs affect economies, health systems, and households and individuals through a range of drivers such as reduced labor productivity, higher medical treatment costs, and lost savings. These drivers aggregate into significant socioeconomic impacts, including in the areas of: country productivity and competitiveness; fiscal pressures; health outcomes; and poverty, inequity and opportunity loss. Despite the magnitude of the NCD challenge, there is considerable space for action. While most countries will not be able to treat their way out of the NCD challenge because of the immense costs such a strategy requires, they can target NCD risk factors and promote healthier lifestyles through focused prevention efforts while also facilitating strategic adaptation measures to mitigate the impact of NCDs on economies, health systems, and households and individuals.